Diversity and Ethnobotanical Importance of Pine Species from Sub-Tropical Forests, Azad Jammu and Kashmir - Kishwar Sultana; Sher Wali Khan; Safdar Ali Shah (Journal of Bioresource Management, 2020)
A general investigation of sub-tropical forests, from Pir Chinasi National Park, Tolipir National Park, Dhirkot Nature Reserve and Banjosa Game Reserve was carried out during different months from February 2008 to May 2010. The relative abundance of species was calculated using line transects of 50m. A total of five different species (Abies pindrow. Cedrus deodara, Pinus wallichiana, Pinus roxburgii and Picea smithiana) from the Pinaceae family were recorded. The main reported use of Cedrus deodara and Pinus wallichiana by the local people was for furniture and construction purposes. Pinus wallichiana was observed as the dominant species from all the selected sites.